EFFORTS TO IMPROVE ELEMENTARY STUDENTS' DIGITAL LITERACY THROUGH THE USE OF TECHNOLOGY-BASED LEARNING MEDIA - Wirda Safitri; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The purpose of this study is to explain efforts to increase digital literacy ofelementary students throughuse of technology-based learning media in socialstudies learning. The research method used a literature study approach. Sourcesof research data are secondary data by collecting research data from severaljournals that are relevant to the topic of discussion. The results of the studyshow that the IPS learning paradigm through the use of various technologybased learning media is carried out so that learning is relevant to the rapiddevelopment of technology. The use of instructional media in social studieslearning varies greatly according to the material delivered by the teacher andthe availability of adequate technological devices. Utilization of technologybased learning media is carried out as a teacher's effort in packaging socialstudies learning material to be more attractive so that the learning processbecomes more interactive and real, effective and efficient as well as fosteringstudent motivation so that it is easy to understand and student-centered learning.The use of technology-based learning media in the learning process contributesto improving elementary students' digital literacy skills. This happens becausethe teacher designs a learning process that involves elementary school studentsto directly use and practice technological devices.